2014
DOI: 10.1186/1471-2164-15-746
|View full text |Cite
|
Sign up to set email alerts
|

De novo leaf and root transcriptome analysis identified novel genes involved in Steroidal sapogenin biosynthesis in Asparagus racemosus

Abstract: BackgroundSaponins are mainly amphipathic glycosides that posses many biological activities and confer potential health benefits to humans. Inspite of its medicinal attributes most of the triterpenes and enzymes involved in the saponin biosynthesis remains uncharacterized at the molecular level. Since the major steroidal components are present in the roots of A. racemosus our study is focussed on the comparative denovo transcriptome analysis of root versus leaf tissue and identifying some root specific transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 44 publications
3
64
0
Order By: Relevance
“…Leaf versus root transcriptome of Asparagus racemosus using Illumina Wang et al (2016aWang et al ( , 2016b 1 3 sequencing approach revealed that majority of transcripts related to steroidal saponin biosynthesis including P450 and UDP-glucosyltransferase was found to be upregulated in root tissue as compared to leaf. This will lead to the hypothesis that steroidal saponin accumulated in the roots of Asparagus racemosus, which is mainly responsible for its pharmacological properties (Upadhyay et al 2014). …”
Section: Asparagus Racemosusmentioning
confidence: 99%
“…Leaf versus root transcriptome of Asparagus racemosus using Illumina Wang et al (2016aWang et al ( , 2016b 1 3 sequencing approach revealed that majority of transcripts related to steroidal saponin biosynthesis including P450 and UDP-glucosyltransferase was found to be upregulated in root tissue as compared to leaf. This will lead to the hypothesis that steroidal saponin accumulated in the roots of Asparagus racemosus, which is mainly responsible for its pharmacological properties (Upadhyay et al 2014). …”
Section: Asparagus Racemosusmentioning
confidence: 99%
“…It was found that the content of triterpenes accumulated in the leaves of P. ginseng are higher in the early growth stage, while the content of triterpenes in the roots of old plants are higher [27]. Comparative transcriptome analysis including root and leaf tissues to excavate transcripts related to saponin biosynthesis is already reported for many plants, such as Hedera helix [28], Panax notoginseng [29] and Asparagus racemosus [26]. The maximum triterpenoid saponin content was identi ed in stem.…”
Section: Introductionmentioning
confidence: 84%
“…Recently, transcriptome assay with next-generation sequencing has been extensively used to explore the novel genes underlying active-ingredient biosynthesis pathways in medicinal plants. Some include the excavation of genes encoding enzymes that catalyze distinct steps related to the biosynthetic pathway of ginsenosides in Panax ginseng [13], triterpenoid saponin biosynthesis in Bacopa monnieri [14], artemisinin in Artemisia annua [15,16], avonoid biosynthesis in sa ower [17], glycyrrhizin in Glycyrrhiza uralensis [18], rubber in Parthenium argentatum [19], cardiac glycoside in Calotropis procera [20], terpenoid in Cinnamomum camphora [21], cannabinoids in Cannabis sativa [22], withanolide in Withania somnifera [23], picrosides in Picrorhiza kurrooa [24], paclitaxel in Taxus chinensis [25] and steroidal saponins in Asparagus racemosus [26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the root of Valeriana fauriei (valerian), which is used for medicinal purposes, the terpenoid biosynthesis genes were highly upregulated [43]. Another plant Asparagus racemosus, whose tuberous roots are used in traditional Indian medicine, showed upregulation of terpenoid biosynthesis genes in roots compared to leaves [44]. On the other hand, in Cymbopogon winterianus (citronella), whose leaves are known to have antimicrobial properties, shows higher expression of terpenoid biosynthesis genes in leaves compared to roots [45].…”
Section: Upregulation Of Genes Involved In Terpenoid Biosynthesis In mentioning
confidence: 99%